1998
DOI: 10.1016/s0969-2126(98)00090-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the C2 domain from protein kinase C-δ

Abstract: The N-terminal sequence of Ca(2+)-independent novel PKCs defines a divergent example of a C2 structure similar to that of phospholipase C-delta. The Ca(2+)-independent regulation of novel PKCs is explained by major structural and sequence differences resulting in three non-functional Ca(2+)-binding loops. The observed structural variation and position of a tyrosine-phosphorylation site suggest the existence of distinct subclasses of C2-like domains which may have evolved distinct functional roles and mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 41 publications
2
80
0
2
Order By: Relevance
“…It is interesting that the 60% of β-sheet calculated for PKCε correlates also well with the percentages calculated by X-ray diffraction for C2 domains of the same topology, such as PLCδ (53%), cPLA2 (60%) and PKCδ-C2 (53%) domains [17,36,44]. Recent studies have shown the crystal structure of the PKCδ-C2 domain, which belongs to the group of novel PKCs.…”
Section: Structure Of the Pkcε-c2 Domainsupporting
confidence: 61%
See 2 more Smart Citations
“…It is interesting that the 60% of β-sheet calculated for PKCε correlates also well with the percentages calculated by X-ray diffraction for C2 domains of the same topology, such as PLCδ (53%), cPLA2 (60%) and PKCδ-C2 (53%) domains [17,36,44]. Recent studies have shown the crystal structure of the PKCδ-C2 domain, which belongs to the group of novel PKCs.…”
Section: Structure Of the Pkcε-c2 Domainsupporting
confidence: 61%
“…Recent studies have shown the crystal structure of the PKCδ-C2 domain, which belongs to the group of novel PKCs. However, the low sequence homology between PKCε and PKCδ C2 domains suggests that further structural variations are expected to be found in this (A) (B) group [17]. For example, there is an extended sequence in the CBR1-like loop of PKCε that could adopt a large loop conformation similar to that described in the CBR1 of PLCδ1, PTEN or PI3K [13,34,36].…”
Section: Structure Of the Pkcε-c2 Domainmentioning
confidence: 96%
See 1 more Smart Citation
“…The domain consists of an anti-parallel ␤-sandwich composed of two four-stranded sheets. The overall fold of the cPLA 2 C2 domain is similar to the C2 domains from other proteins: synaptotagmin I (SytI-C2A) (21), phospholipase C␦1 (22), protein kinase C␦ (23), and protein kinase C␤ (24). The topology of the domain is identical to that of phospholipase C␦1 and the recently reported calcium-independent C2 domain from protein kinase C␦ (23), whereas it is a circular permutation of the SytI-C2A and protein kinase C␤ topology.…”
mentioning
confidence: 86%
“…Interestingly, the novel C2 domain factor has only 7 β strands (Fig. 2) in comparison with 8 stranded β-sandwich in other C2 domains of C2-domain superfamily proteins, such as PLC-δ, SynC2A, cPLA2, PKC-δ and PKC-β (Sutton et al, 1995;Essen et al, 1996;Perisic et al, 1998;Sutton and Sprang, 1998;Pappa et al, 1998). Also, the four putative proteins in zebrafish (GenBank accession no.…”
Section: Screening Cloning and Characterization Of A Novel C2 Domainmentioning
confidence: 99%